The thermoluminescence characteristics and the glow curves of thulium doped silica fiber exposed to 10 MV photon and 21 MeV electron radiation - Ariffin, Alawiah; M. S., Alina; Bauk, Sabar; Abdul Rashid, Hairul Azhar; Gieszczyk, Wojciech; Mohd Noor, Noramaliza; Mahdiraji, Ghafour Amouzad; Tamchek, Nizam; Zulkifli, M. I.; Bradley, David Andrew; Marashdeh, Mohammad Wasef Mohammad (Elsevier, 2015)
The thermoluminescence (TL) glow curves and kinetics parameters of Thulium (Tm) doped silica cylindrical fibers (CF) are presented. A linear accelerator (LINAC) was used to deliver high-energy radiation of 21 MeV electrons and 10 MV photons. The CFs were irradiated in the dose range of 0.2–10 Gy. The experimental glow curve data was reconstructed by using WinREMS. The WinGCF software was used for the kinetic parameters evaluation. The TL sensitivity of Tm-doped silica CF is about 2 times higher as compared to pure silica CF. Tm-doped silica CF seems to be more sensitive to 21 MeV electrons than to 10 MV photons. Surprisingly, no supralinearity was displayed and a sub-linear response of Tm-doped silica CF was observed within the analyzed dose range for both 21 MeV electrons and 10 MV photons. The Tm-doped silica CF glow curve consists of 5 individual glow peaks. The Ea of peak 4 and peak 5 was highly dependent on dose when irradiated with photons. We also noticed that the electron radiation (21 MeV) caused a shift of glow peak by 7–13 °C to the higher temperature region compared with photons radiation (10 MV). Our Tm-doped fibers seem to give high TL response after 21 MeV electrons, which gives around 2 times higher peak integral as compared with 10 MV photon radiation. We concluded that peak 4 is the first-order kinetic peak and can be used as the main dosimetric peak of Tm-doped silica CF.